Implementation of Supply Chain Management in Web-Based Support Systems Employee Recruitment in Private Hospitals - Musran Munizu; Muh. Risal Tawil; Giatika Chrisnawati; Helson Hamid; Muhammad Lukman Hakim (SEULANGA SYSTEM PUBLISHER, 2023)
This public hospital still has many weaknesses in recruiting employees, so the time needed for hiring employees is long and not organized properly, which hampers the need for employees. Therefore, in order to support the smooth running of the employee recruitment system, it is necessary to create an executive support system that can provide solutions for the process of employee recruitment activities at the hospital later. To design an executive support system, a literature study, interviews with executives, observations, and final test results are calculated using a rule-based expert system. The proposed executive information system design includes a model design, data design, dialogue design, and implementation plan. The approach employed in this research is the object-oriented system development approach utilizing the Unified Modeling Language (UML) design tool and the waterfall strategy system development model. The programming languages utilized are Hypertext Preprocessor (PHP) and My Structure Query Language (MySQL). The outcome of this investigation is a web-based information system for supply chain management that can assess potential new hires and merge internal departments to enhance the seamless flow of information and the approval of candidate reports.